Analisis Hiperbola dan Sinekdot dalam Pidato Politik Jokowi Tahun 2014 dan 2015 disiarkan langsung di Metro TV - Jaftiyatur Rohaniyah; Saimatul Fadilah (Wacana Didaktika, 2018)
Speeches became an important media for a president like Joko Widodo (Jokowi) to deliver messages, persuade people, influence audience. The speech making process involved a long discussion between Jokowi and a particular team since they should consider some language aspects such as lexical choices and sentence structure in order to achieve certain goals. With regard to this, languages in speeches became important to be analyzed. There are two objects that will be analyzed. These are: kind of hyperbole and synecdoche expression are used by Jokowi in his two political speeches and How is the utterance of hyperbole and synecdoche expression used in the two of Jokowi’s political speeches. The research data consisted of two selected speeches delivered by Jokowi in APEC CEO summit 2014 forum held in November 10, 2014 and the speech delivered in Asian-African Conference Commemoration (AACC) held from 19-21 April 2015. While the research method was a descriptive qualitative research. The data in this research were speech videos downloaded from www.youtube.com. The videos were then transcribed and analyzed. The main research instrument was the researcher himself supported by the data analysis sheet. The data analysis was performed by categorizing the data based on Figurative language categorization which hyperbole and synecdoche. The finding of this research, the resercher found 18 expression in the two of Jokowi’s speeches (APEC CEO SUMMIT 2014 and Asian-Affrican Conference Commemoration 2015). In 2014 Jokowi use 11 figurative expressions from 5 expression in hyperbole and 6 expressions in synecdoche. In 2015, jokowi less use figurative expression. The language that he used was mostly natural language. The figurative language he used in his political speech at 2015 only found 7 expressions; 3 expression of hyperbole and 4 expression of synecdoche. Keywords: Hyperbole, Synecdoche, and Political Speech Abstract: Sebuah Pidato merupakan media yang penting bagi seorang President seperti Joko Widodo dalam menyampaikan pesan, mengajak seseorang dan dapat memberi pengaruh terhadap audien. Sebuah pidato kepresidenan melewati proses yang panjang antara Jokowi dan team tertentu karena harus mempertimbangkan beberapa aspek kebahasaan seperti pemilihan kata secara leksikal dan susunan kalimat agar dapat menyampaikan beberapa tujuan. Sehingga, sehubungan dengan ini, bahasa dalam sebuah pidato menjadi penting untuk dianalisa. Ada dua focus penelitian (1) apa saja ungkapan hyperbola dan synecdoche yang disampaikan Jokowi dalam pidato politiknya? (2) apa makna sesungguhnya dari beberapa ungkapan hiperbola dan synecdoche dalam pidato politik Jokowi?. Dalam hal ini, ada dua pidato terpilih untuk dianalisa yaitu pidato yang disampaikan Jokowi di acara APEC CEO summit 2014 forum dan di Asian-African Conference Commemoration (AACC) 2015. Metode penelitian ini adalah metode deskriptif kualitatif. Data dalam penelitian ini adalah bersumber dari video yang didapat dari www.youtube.com yang kemuadian di transcripkan kedalam bentuk tulisan untuk dianalisa. Instrumen utama penelitian ini adalah peneliti sendiri yang didukung oleh lembaran analisis. Hasil dari penelitian ini adalah peneliti menemukan 18 ungkapan dalam 2 pidato Jokowi (APEC CEO SUMMIT 2014 dan Asian-Affrican Conference Commemoration 2015). Pada tahun 2014 Jokowi menggunakan 11 ungkapan figuratif yaitu ada 5 kalimat hiperbola dan 6 ungkapan sinekdos. Pada tahun 2015, Jokowi kurang menggunakan ungkapan figuratif. Bahasa yang digunakan cendrung pada bahasa natural. Di tahun tersebut, ungkapan figuratif hanya ditemukan 7 ungkapan: 3 ungkapan hiperbola dan 4 ungkapan sinecdoc.